ANALISIS TINGKAT AKTIVITAS FISIK DAN KEBUGARAN JASMANI SISWA SEKOLAH DASAR DI WILAYAH PERKOTAAN SEBAGAI LANDASAN STRATEGI PEMBELAJARAN PJOK - Wuragil Kuning, Proboningrum; Alfan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical activity and physical fitness are fundamental aspects of growth and development for elementary school students, particularly in urban areas prone to sedentary behavior. This study aims to map the physical activity and fitness profiles of third-grade students at SDN Pengalaman 1 Malang as a basis for developing a physical education (PJOK) learning strategy. Using a quantitative descriptive approach with 26 respondents, physical activity was measured using the PAQ-C instrument, while physical fitness was measured using the TKSI Phase B. The analysis results show that students' physical activity is in the moderate category (mean score of 2.82), with 57.7% of students having a similar level of physical fitness. This condition indicates the need to strengthen PJOK learning that is more dynamic, varied, and enjoyable. These findings are expected to be a reference for teachers in designing learning based on student needs, while supporting the implementation of the National Sports Grand Design (DBON) to improve the physical fitness of Indonesian students.